Perjanjian Perkawinan Sebagai Perlindungan Hukum Terhadap Harta Bersama Akibat Perceraian - Lukman; Nasution, Romadon; Rotamaro, Sahnan; Fadillah, Ardana (Tabayyun : Journal Of Islamic Studies, 2024)
This journal discusses the importance of a marriage agreement to protect shared assets when couples divorce. Marriage is crucial in human life as it involves the relationship between spouses and children. The research emphasizes how the law can help safeguard shared assets of divorcing couples. The journal also explains the concept of naskh in the Quran and fiqh related to marriage agreements. The aim of this research is to provide a deeper understanding of Marriage Agreements as Legal Protection of Shared Assets Due to Divorce, viewed from the perspectives of fiqh law and positive law.